Chemical composition and bioactivity of dried fruits and honey of Ficus carica cultivars Dottato, San Francesco and Citrullara. (24th January 2014) - Loizzo, Monica R; Bonesi, Marco; Pugliese, Alessandro; Menichini, Francesco; Tundis, Rosa
Abstract BACKGROUND The aim of this study is to evaluate, for the first time, the chemical profile, antioxidant properties and cholinesterase inhibitory activity of dried fruits and honey of Ficus carica (fig) cultivars Dottato, Citrullara, and San Francesco. RESULTS Gas chromatography–mass spectrometry (GC‐MS) analysis of fig extracts identified terpenes, sterols and fatty acids as major constituents. The aroma profile of honey obtained from a mixture of the three cultivars was investigated by solid‐phase micro‐extraction/GC‐MS. 5‐(Hydroxymethyl)‐2‐furancarboxaldehyde, 2, 3‐dihydro‐3, 5‐dihydroxy‐6‐methyl‐4H‐pyran‐4‐one and 1, 3‐dihydroxy‐2‐propanone were the main compounds. Total phenol, flavonoid and anthocyanin content are also reported. The San Francesco cultivar is characterised by the highest phenol and flavonoid content, while Dottato showed the major anthocyanin content. The Dottato cultivar exhibited the best radical scavenging activity against both 2, 2′‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonic acid) and 2, 2‐diphenyl‐1‐picrylhydrazyl radicals (IC50 values of 5.4 and 22.6 µg mL−1, respectively). This cultivar also showed the highest inhibitory activity against both acetylcholinesterase and butyrylcholinesterase, with IC50 values of 26.9 and 31.8 µg mL−1, respectively. CONCLUSION Dried figs are a convenient source of bioactive compounds that demonstrated potential neuroprotection and antioxidant effects. Therefore, the addition of figs to the human diet should be recommended by dieticians and nutritionists. © 2013 Society of Chemical Industry